1996
DOI: 10.1046/j.1524-475x.1996.40405.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone replacement on wound healing in healthy older men

Abstract: The secretion of growth hormone, an important anabolic agent, declines with aging. We hypothesize that growth hormone levels (measured as insulin-like growth factor-1) correlate with postoperative tissue repair in otherwise healthy, elderly persons. The goal was to determine whether growth hormone supplementation can improve wound healing in this circumstance. We conducted a randomized controlled double-blind trial of 6 months of growth hormone replacement or placebo in 28 healthy older men (>69 years of age) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…The well-known anabolic actions of GH have also led to use in patients in severe catabolic states, such as surgery[12], trauma[13], burns[14], intestinal fistula[15] and short bowl syndrome[16],[17]. GH has been also used to overcome apparent resistance and reverse protein catabolism that leads to muscle weakness, impaired wound healing[18] and immune responses[19],[20], resulting in increased mortality. But data from Japan suggested a possibly increased risk of leukemia in children treated with GH.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known anabolic actions of GH have also led to use in patients in severe catabolic states, such as surgery[12], trauma[13], burns[14], intestinal fistula[15] and short bowl syndrome[16],[17]. GH has been also used to overcome apparent resistance and reverse protein catabolism that leads to muscle weakness, impaired wound healing[18] and immune responses[19],[20], resulting in increased mortality. But data from Japan suggested a possibly increased risk of leukemia in children treated with GH.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated an increase in muscle mass, but not in muscle strength, others have shown an increase in both muscle mass and strength after administration of GH supplementation [347, 348]. In addition, the combination of GH replacement and exercise training does not improve the effects brought by exercise alone [349].…”
Section: Intervention Strategies To Counteract Disability Associatmentioning
confidence: 99%
“…1996 ;4 :297-303 -(see Fu et al). 1996 ;4 :381-5 Tierney MJ (see Papadakis et al). 1996 ;4 :421-5 Tintle T (see Mulder et al).…”
mentioning
confidence: 99%